Reversible data hiding in encrypted images for coding channel based on adaptive steganography. Issue 16 (23rd February 2021) - Yu, Kunliang; Chen, Liquan; Wang, Yu; Han, Jinguang; Zhang, Lejun
Abstract : In this study, a novel reversible data hiding (RDH) in encrypted domain scheme for coding channel based on sliding‐block segmentation and adaptive steganography is proposed. The proposed scheme enriches the residual information with as little additional encryption information as possible to improve the testing error rate of a steganalyser by sliding‐block segmentation with bit stream encryption. The specific encryption process effectively weakens the correlation between the adjacent pixels and minimises the size of key stream bits. The encryption key can be further embedded in the channel code stream before transmitted in the channel. Experimental analysis shows that the image encrypted by the proposed RDH scheme can achieve a peak‐signal‐to‐noise ratio of >50 dB, as the payload is 0.5 bits per pixel (bpp). In terms of security performance, compared with the state‐of‐the‐art methods, their method has a higher testing error rate when the steganalyser is utilised. Even if the payload is 0.5 bpp, the testing error rate is >0.25.